Chemokines and their receptors in the esophageal carcinoma tumor microenvironment: key factors for metastasis and progression - Liu, Pan; Sun, Zhiqiang (Frontiers in Oncology, 2025)
Esophageal carcinoma (ESCA) is a highly malignant tumor with the highest incidence in Eastern Asia. Although treatment modalities for ESCA have advanced in recent years, the overall prognosis remains poor, as most patients are diagnosed at an advanced stage of the disease. There is an urgent need to promote early screening for ESCA to increase survival rates and improve patient outcomes. The development of ESCA is closely linked to the complex tumor microenvironment (TME), where chemokines and their receptors play pivotal roles. Chemokines are a class of small-molecule, secreted proteins and constitute the largest family of cytokines. They not only directly regulate tumor growth and proliferation but also influence cell migration and localization through specific receptor interactions. Consequently, chemokines and their receptors affect tumor invasion and metastatic spread. Furthermore, chemokines regulate immune cells, including macrophages and regulatory T cells, within the TME. The recruitment of these immune cells further leads to immunosuppression, creating favorable conditions for tumor growth and metastasis. This review examines the impact of ESCA-associated chemokines and their receptors on ESCA, emphasizing their critical involvement in the ESCA TME.